Extended Kalman Filter-Based Approach for Autonomous Synchronization and Ranging in GPS-Denied Environments - Xiaobo Gu; Weiqiang Tan; Di Zhang; Yudong Lu; Ruidian Zhan (Complexity)
Network ranging and clock synchronization based on two-way timing stamps exchange mechanism in complex GPS-denied environments is addressed in this paper. An estimator based on the Extended Kalman filter (EKF) is derived, according to which, the clock skew, clock offset, and ranging information can be jointly estimated. The proposed estimator provides off-line computation by storing the transmitting timing stamps in advance and could be implemented in asymmetrical and asynchronous scenarios. The simulation results show that the proposed estimator achieves a relative good performance than the existed estimators. In addition, a new Bayesian Cramér–Rao Lower Bound (B-CRLB) is derived. Numerous simulation results show that the proposed estimator meets the B-CRLB.